Population genetics of Glossina palpalis gambiensis in the sleeping sickness focus of Boffa (Guinea) before and after eight years of vector control: no effect of control despite a significant decrease of human exposure to the disease - Kagbadouno, Moise S; Séré, Modou; Ségard, Adeline; Camara, Abdoulaye Dansy; Camara, Mamadou; Bucheton, Bruno; Bart, Jean-Mathieu; Courtin, Fabrice; De Meeûs, Thierry; Ravel, Sophie (Peer Community Journal)

(untitled)
Human African trypanosomosis (HAT), also known as sleeping sickness, is still a major concern in endemic countries. Its cyclical vector are biting insects of the genus Glossina or tsetse flies. In Guinea, the mangrove ecosystem contains the main HAT foci of Western Africa. There, the cyclical vector is Glossina palpalis gambiensis. A still ongoing vector control campaign (VCC) started in 2011 in the focus of Boffa, using tiny targets, with a 79% tsetse density reduction in 2016 and significant impact on the prevalence of the disease (from 0.3% in 2011 to 0.11% in 2013, 0.0352% in 2016 and 0.0097% in 2019). To assess the sustainability of these results, we have studied the impact of this VCC on the population biology of G. p. gambiensis in Boffa. We used the genotyping at 11 microsatellite markers and population genetic tools of tsetse flies from different sites and at different dates before and after the beginning of the VCC. In variance with a significant impact of VCC on the apparent densities of flies captured in the traps deployed, the global population of G. p. gambiensis displayed no variation of the sex-ratio, no genetic signature of control, and behaved as a very large population occupying the entire zone. This implies that targets deployment efficiently protected the human populations locally, but did not impact tsetse flies where targets cannot be deployed and where the main tsetse population exploits available resources. We thus recommend the pursuit of vector control measures with the same strategy, through the joint effect of VCC and medical surveys and treatments, in order to protect human populations from HAT infections until the disease can be considered as entirely eradicated from the focus.